Serotonergic Regulation of Corticoamygdalar Neurons in the Mouse Prelimbic Cortex - Avesar, Daniel; Stephens, Emily K.; Gulledge, Allan T. (Frontiers in Neural Circuits, 2018)
Neuromodulatory transmitters, such as serotonin (5-HT), selectively regulate the excitability of subpopulations of cortical projection neurons to gate cortical output to specific target regions. For instance, in the mouse prelimbic cortex, 5-HT selectively excites commissurally projecting (COM) intratelencephalic neurons via activation of 5-HT2A (2A) receptors, while simultaneously inhibiting, via 5-HT1A (1A) receptors, corticofugally projecting pyramidal neurons targeting the pons. Here we characterize the physiology, morphology, and serotonergic regulation of corticoamygdalar (CAm) projection neurons in the mouse prelimbic cortex. Layer 5 CAm neurons shared a number of physiological and morphological characteristics with COM neurons, including higher input resistances, smaller HCN-channel mediated responses, and sparser dendritic arbors than corticopontine neurons. Across cortical lamina, CAm neurons also resembled COM neurons in their serotonergic modulation; focally applied 5-HT (100 µM; 1 s) generated 2A-receptor-mediated excitation, or 1A- and 2A-dependent biphasic responses, in ipsilaterally and contralaterally projecting CAm neurons. Serotonergic excitation depended on extrinsic excitatory drive, as 5-HT failed to depolarize CAm neurons from rest, but could enhance the number of action potentials generated by simulated barrages of synaptic input. Finally, using dual tracer injections, we identified double-labeled CAm/COM neurons that displayed primarily excitatory or biphasic responses to 5-HT. Overall, our findings reveal that prelimbic CAm neurons in layer 5 overlap, at least partially, with COM neurons, and that neurons projecting to either, or both targets, exhibit 2A-dependent serotonergic excitation. These results suggest that 5-HT, acting at 2A receptors, may promote cortical output to the amygdala.